Protection System for LVDC Distribution Networks Using a Fault Current-Limiting Converter and Protection Zones - Jin-Su Kim; Eun-Chul Lee; Sang-Yun Yun (IEEE Access, 2023)
In this study, we propose a generalized protection system for low-voltage DC (LVDC) distribution networks based on fault current-limiting (FCL) and the concept of protection zones (PZs). The proposed system ensures fault resilience and sufficient operating time for protection devices (PDs) through the FCL of the power conversion device, and it performs protection coordination through fault zone isolation. FCL is achieved using a buck converter-type fault current-limiter to actively control the DC-side fault current contribution of the rectifier, as well as a phase-shift dual-active-bridge (DAB) converter, which exhibits inherent limiting effects during faults. This also enables PZ isolation. In addition, we propose a relaying method to coordinate protection in each PZ. The system distinguishes the types of arbitrary PDs that form each PZ according to their position within the PZ and defines predetermined relaying methods and operation criteria for each type. This enables the protection system to be easily configured for new systems or changing system topology. We configure an LVDC system using a general DC circuit breaker that does not rely on communication signals and generalize its relaying method for each PZ. We verified the applicability of the proposed method to real networks using MATLAB/Simulink simulations and in a hardware-in-the-loop simulation environment with actual manufactured DAB converter controllers and DC circuit breaker relays. In addition, a comparison with existing methods showed that the proposed method could contribute to improving supply reliability by reducing the frequency of system interruption despite lower infrastructure investment.